Transforming Arabic Academic Writing Competence through ADDIE-Based Instructional Design: A Developmental Study - Mirza, Aidha Zalidar; Zunairoh, Yuyun; Ahid, Nur (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
Despite mastering foundational grammar, non-native Arabic learners in higher education frequently encounter severe cognitive and structural paralysis when attempting to produce peer-reviewed academic research articles. This study aims to develop, validate, and evaluate the empirical effectiveness of specialized ADDIE-based instructional materials tailored for Arabic academic writing. Employing a Research and Development (R&D) design, the study involved an exhaustive sample of 37 sixth-semester students at KH. Abdul Wahab Hasbullah University. The developmental phase produced a comprehensive seven-chapter module focusing on the anatomical structure of scientific papers, pre-writing operations, and academic metadiscourse. Instructional efficacy was measured using a one-group pretest-posttest experimental design. Inferential statistical analysis revealed a highly significant improvement in students’ academic writing competencies (p < 0.001), with mean scores surging from a baseline of 37.84 to 86.43 following the intervention. Furthermore, the Normalized Gain (N-Gain) analysis yielded a score of 0.77 (76.99%), definitively classifying the module’s pedagogical impact as “High.” In conclusion, the systematic scaffolding provided by the ADDIE framework successfully dismantles students’ writing apprehension, bridging the critical gap between mechanical language acquisition and rigorous academic knowledge production.